Emanuel Halicz: The 1863 Polish Uprising and Scandinavia. The Year 1863, The Turning-Point in Russo-Scandinavian Relations. (Københavns Universitets Slaviske Institut. Rapporter, bd. 17, 1988). 169 - Amstrup, Niels (Historie/Jyske Samlinger, 1991)
-